2nd EAA International Symposium on Hydroacoustics - Archives of Acoustics, Editorial Board (Archives of Acoustics, 1998)
The Symposium is jointly organised by the Technical University of Gdańsk and the Naval Academy in Gdynia under the auspices of the European Acoustical Association, and sponsored by the Polish National Committee for Scientific Research. The Symposium will include invited and contributed papers on the following topics: •Ambient and ship noise, •Reverberation and scattering, •Sound propagation modelling, •Sonar systems and data processing, •Non-linear acoustics, •Acoustics in fisheries, •Transducers and instrumentation. The working language of the Symposium will be English (for both the manuscripts and the oral presentations).